Raspberry Pi : making amazing projects right from scratch! : explore the powers of Raspberry Pi and build your very own projects right out of the box : a course in three modules.: making amazing projects right from scratch! : explore the powers of Raspberry Pi and build your very own projects right out of the box : a course in three modules. (2016) - Pajankar, Ashwin; Kakkar, Arush; Poole, Matthew (Matthew David); Grimmett, Richard
No abstract available